2016
DOI: 10.1080/09168451.2016.1189321
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of MAK-1 and MAK-2 MAP kinases in cell wall integrity in Neurospora crassa

Abstract: Among three MAPK disruptants of Neurospora crassa, Δmak-1 was sensitive and Δmak-2 was hypersensitive to micafungin, a beta-1,3-glucan synthase inhibitor, than the wild-type or Δos-2 strains. We identified six micafungin-inducible genes that are involved in cell wall integrity (CWI) and found that MAK-1 regulated the transcription of non-anchored cell wall protein gene, ncw-1, and the beta-1,3-endoglucanase gene, bgt-2, whereas MAK-2 controlled the expression of the glycosylhydrolase-like protein gene, gh76-5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…The most interesting thing is that both phosphorylated and total MAK-1 proteins were undetected in all deletion mutants of kinases belonging to the PR-MAP kinase pathway (the nrc-1, mek-2, and mak-2 mutants) during protoperithecium development. This is similar to the result of Kamei et al (2016), in which the phosphorylation of MAK-1 was undetected in the mak-2 mutant from conidial germination to hyphal development. Recent studies showed that proper fruiting body development in N. crassa was dependent on the MAK-2-phosphorylated N-terminus of MOB-3, a member protein of the STRIPAK complex, which impacts the nuclear accumulation of MAK-1 (Dettmann et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…The most interesting thing is that both phosphorylated and total MAK-1 proteins were undetected in all deletion mutants of kinases belonging to the PR-MAP kinase pathway (the nrc-1, mek-2, and mak-2 mutants) during protoperithecium development. This is similar to the result of Kamei et al (2016), in which the phosphorylation of MAK-1 was undetected in the mak-2 mutant from conidial germination to hyphal development. Recent studies showed that proper fruiting body development in N. crassa was dependent on the MAK-2-phosphorylated N-terminus of MOB-3, a member protein of the STRIPAK complex, which impacts the nuclear accumulation of MAK-1 (Dettmann et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, mitogen‐activated protein kinases (MAP kinases) are known to be involved in multifunctional and diverse signalling pathways, including cell wall integrity [26], cell‐to‐cell communication [13], circadian regulation of cellular processes [11, 12], phosphate signalling [27] and sensing of osmolarity and carbon [28] in N. crassa . We confirmed that three MAP kinases had been identified with existing acetylation sites, including MAK‐1, MAK‐2, and HOG‐1, indicating that these three MAP kinases may have been acetylated to participate in regulating multifunctional and various signalling pathways.…”
Section: Figurementioning
confidence: 99%
“…To better ascertain the functions of acetylation proteins, we further classified the identified proteins involvement in diverse signalling pathways (Table S2) Furthermore, mitogen-activated protein kinases (MAP kinases) are known to be involved in multifunctional and diverse signalling pathways, including cell wall integrity [26], cell-to-cell communication [13], circadian regulation of cellular processes [11,12], phosphate signalling [27] and sensing of osmolarity and carbon [28] in N. crassa. We con- Moreover, we identified the casein kinases, including the casein kinase I isoform delta (CK-1a), casein kinase 1b (CK-1b) and casein kinase II subunit alpha (CKα) has having acetylation sites, and interestingly, CK-1a had nine acetylation sites distributed in the N terminus.…”
mentioning
confidence: 99%
“…Ssd1 functions in parallel to Mpt5 (another RBP) to maintain CWI (Kaeberlein and Guarente, 2002 ). In N. crassa , the conserved CWI pathway is activated under cell-wall stress conditions and modulated by different proteins, including a Mitogen-Activated Protein-Kinase (MAPK) cascade that is comprised of MIK-1 (NCU02234), MEK-1 (NCU06419), and MAK-1 (NCU09842) (Park et al, 2008 ; Bennett et al, 2013 ; Kamei et al, 2016 ). This pathway can alter the transcription of multiple genes via the transcription-factor ADV-1 (NCU07392), encoded by a gene that is conserved among the Pezizomycotina and is essential for germling communication and fusion (Leeder et al, 2013 ; Dekhang et al, 2017 ; Fischer et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%